Tuesday

September 2, 2014

September 2, 2014

Posted by **jen** on Saturday, September 4, 2010 at 2:02pm.

- algebra -
**Henry**, Saturday, September 4, 2010 at 7:49pm2x^2 - 3x + 6 = 0.

x = 3+- sqrt(9 - 48) / 4 =

3 +- sqrt(-39) / 4 =

(3 +- sqrt(39*-1)) / 4

sqrt(-1) = i

x = +- isqrt(39) / 4

Solution Set:

x =(3 - isqrt(39)) / 4

x =(3 + isqrt(39)) / 4

**Answer this Question**

**Related Questions**

Math - Use the quadratic formula to solve each of the following quadratic ...

algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...

math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...

Algebra - Use the Quadratic formula to solve the equation -4x^2-3x+2=0

algebra - Use the quadratic formula to solve the equation. x^2-7x-6=0

algebra 1 - Use the Quadratic Formula to solve the equation: 5x^2 - 6x - 8=0 -....

algebra 1 - Use the Quadratic Formula to solve the equation: 5x^2 + 9x - 2=0 -2...

algebra - Use the quadratic formula to solve the equation x^2-5x=-10

algebra - use the quadratic formula to solve the equation 4x^2-7x-2=0

algebra - Solve the quadratic equation: 2x(squared)+6x+12=0 I know you have to ...